Kendala Pembelajaran Jarak Jauh (PJJ) Secara Online Selama Masa Pandemik Covid-19 di Sekolah Dasar - Dian Primasari, Ika Firma Ningsih; Zulela, Zulela (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
The purpose of this study was to obtain information on the constraints of distance learning (PJJ) during the Covid-19 pandemic in elementary schools. This research uses an exploratory case study method and the research approach uses a qualitative case study method. In this study, respondents were 5 people, consisting of two teachers, namely a teacher at SDN 01 Cirendeu and a teacher at SD Negeri Pondok Cabe Udik 01 and three parents of students in an elementary school in South Tangerang. Semi-structured interviews were conducted and a list of questions compiled for interviews was developed based on related literature. The validity of the data in this study used triangulation in the data collection method, through interviews with 5 informants, namely teachers and parents. The data analysis technique uses thematic analysis. The results of the research are constraints on the availability of learning media (mobile phones, computers, or laptops), lack of mastery of science and technology (science and technology), cost constraints for purchasing internet packages (quota), time constraints (the need for additional time to accompany children to learn from home and time. which contradicts working parents), the added constraints/burdens for parents to teach their children at home cause stress for parents and also feel more irritable. Barriers to communication and socialization between students, teachers, and parents are reduced and the constraints on working hours are unlimited for teachers because they have to communicate intensely and coordinate with parents, other teachers, and school principals.